Intertextuality in the Lento (Assai) from Villa-Lobos’ Symphony no.8 (Orfeu, 2017)
This text consists of the analysis ofintertextual aspects present in the Lento (Assai) of Symphony n. 8 by Heitor Villa-Lobos (1887-1959), composed in 1950.A discussion about the effect of intertextual relations is presented, including the composer’s musical influences, contexts, other composers with whom Villa-Lobos converses, and the way in which this happens. The intertextual phenomenon inmusic is approached through traditional analysis related to intertextual concepts, presented in categories. These categories include gestural, motivic and stylized. The elements related to stylization, especially in regards to Brazilian popular music, will be discussed through musical topics.
Keywords: Intertextuality in music; Symphonies; Musical analysis; Heitor Villa-Lobos